Semi-elemental versus polymeric formula for enteral nutrition in critically ill patients: a secondary analysis of a multicenter cluster-randomized controlled trial - Wei, Wei; Lu, Wen; Chen, Guofeng; Gao, Jindan; Zhang, Jun; Zhang, Defeng; He, Ruiqin; Huang, Jingjing; Cai, Rong; Yuan, Rongrong; Wang, Xun; Yu, Jinxia; et al. (Frontiers in Nutrition, 2025)
ObjectivesSemi-elemental enteral nutrition (EN) might theoretically improve gastrointestinal tolerance in critically ill patients; however, it is associated with an increased risk of diarrhea when delivered postpylorically. This study aimed to assess whether the use of semi-elemental formula compared to polymeric formula may provide benefits in patients receiving gastric tube feeding.MethodsThis is a post-hoc analysis of data from a multicenter, cluster-randomized, controlled, investigator-initiated trial (NEED trial). Patients were eligible if they stayed in the participating intensive care units (ICUs) and received gastric EN exclusively during the first week of enrollment. A directed acyclic graph (DAG) was used to identify potential confounders. Propensity score matching (PSM) was applied to control for the detected confounders. The primary outcome was the incidence of intolerance-related symptoms, including nausea/vomiting, aspiration, abdominal distension/pain, and diarrhea.ResultsPSM created 516 matched pairs from 1,548 eligible patients. The incidence of abdominal distension/pain was significantly lower in the semi-elemental group compared to the polymeric group (9.1% versus 13.8%, risk ratio, 0.66; 95% CI, 0.46 to 0.93; p = 0.027). No significant differences were observed in the incidence of nausea/vomiting, aspiration, or diarrhea between groups.ConclusionIn critically ill patients receiving EN via gastric access, the semi-elemental formula was associated with a reduced incidence of abdominal distension/pain, but not with an increased incidence of diarrhea, compared to the polymeric formula.Clinical trial registrationhttps://www.isrctn.com/ISRCTN12233792?q=ISRCTN12233792&filters=&sort=&offset=1&totalResults=1&page=1&pageSize=10, Identifier ISRCTN12233792.